2002
DOI: 10.1128/iai.70.11.5903-5912.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interleukin-12 and CD40 Ligand Activities but ReducedStaphylococcus aureusCowan 1-Induced Responses Suggest a Generalized and Progressively Impaired Type 1 Cytokine Pattern for Human Schistosomiasis

Abstract: Whole-blood-cell cultures from schistosomiasis patients were stimulated with a variety of T-cell-dependent and T-cell-independent stimuli to determine whether the defect in type 1 cytokine expression observed following helminth infection is associated with alterations in interleukin-12 (IL-12) or CD40 ligand (CD40L) responsiveness. Cultures from uninfected individuals produced abundant gamma interferon in response to Staphylococcus aureus Cowan 1 (SAC), while patients with intestinal and hepatosplenic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The second study of TLR-mediated cytokine profiles was carried out in Brazil and also corresponds with our results. Although they did not highlight it, Montenegro et al showed that 48 h whole blood cultures from S. mansoni -infected adults produced more TNF-α than those of uninfected adults in response to LPS [48] .…”
Section: Discussionmentioning
confidence: 99%
“…The second study of TLR-mediated cytokine profiles was carried out in Brazil and also corresponds with our results. Although they did not highlight it, Montenegro et al showed that 48 h whole blood cultures from S. mansoni -infected adults produced more TNF-α than those of uninfected adults in response to LPS [48] .…”
Section: Discussionmentioning
confidence: 99%